Surface modified sodium silicate based superhydrophobic silica aerogels prepared via ambient pressure drying process - Khedkar, Mangesh V.; Somvanshi, Sandeep B.; Humbe, Ashok V.; Jadhav, K.M. (Journal of non-crystalline solids, 2019)
The silica aerogel was synthesized by simple and cost-effective sol-gel process under ambient pressure drying. The wet gel was modified by using trimethylchlorosilane (TMCS) as silylating agent. The prepared aerogel was characterized by X-ray diffractometer (XRD), thermogravimetric and differential thermal analyzer (TG-DTA), Fourier transform infrared spectrometer (FT-IR), Brunauer-Emmett-Teller (BET) analyzer, field emission scanning electron microscope (FE-SEM) and Ultraviolet-Visible (UV–Vis) spectrophotometer for structural, thermal, functional, surface, morphological and optical properties. The presence of hump in X-ray diffraction pattern revealed the amorphous nature of prepared silica aerogel. Thermal stability of silica aerogel investigated by TG-DTA show a hydrophobic nature up to 478 °C. FE-SEM images confirmed the porous nature of silica aerogel. The surface area and pore radius measured by BET analyzer disclosed as 792.308 m2/g and 5.779 nm respectively while the total pore volume is 2.289 cc/g. Superhydrophobic nature of silica aerogel sample was affirmed by contact angle measurements. The energy band gap calculated from UV–Vis spectra was found to be 4.25 eV confirming the insulating nature of prepared silica aerogel. The resulting silica aerogel possesses high thermal stability, Superhydrophobicity and large specific surface area which can be useful in various applications such as catalysis, coating materials, oil spill cleanup processes and insulating materials. [Display omitted] •Synthesis of silica aerogel by simple and economic ambient pressure drying method.•Trimethylchlorosilane (TMCS) used as a silylating agent for surface modifications.•Prepared aerogels shown high thermal stability with respect to hydrophobicity.•Brunauer-Emmett-Teller analysis disclosed large surface area of prepared aerogel.•High contact angle value affirmed the superhydrophobic nature of the aerogel.